Voltammetric analysis of glycoproteins containing sialylated and neutral glycans at pyrolytic graphite electrode - Trefulka, Mojmír; Černocká, Hana; Staroňová, Tatiana; Ostatná, Veronika (Bioelectrochemistry (Amsterdam, Netherlands), 2025)
Recently, it was described that neutral glycans can be distinguished from those containing sialic acid at the mercury electrode after modification with osmium(VI) N,N,N',N'-tetramethylethylenediamine (Os(VI)tem). Our work shows the possibility of studying glycans and glycoproteins at pyrolytic graphite electrodes depending on thepresence of sialic acid. Short glycans, glycans released from glycoproteins, and glycoproteins themselves yielded similar voltammetric responses after their modification by Os(VI)tem. Os(VI)tem modified glycans and glycoproteins produced acouple of cathodic and anodic peaks. Changing peak heights and potentials of glycans and glycoproteins pointed out the presence of sialic acid. These findings could be utilized to improve glycoprotein sensing by chemical modification.
Keywords: Polysaccharides; N-Acetylneuraminic Acid; polysacharidy; Electrochemical Techniques; glykoproteiny; Osmium(VI) complexes; Sialoglycoproteins; elektrody; N-acetyl neuraminic acid; zvířata; Animals; Electrodes; Graphite; Electrochemical analysis; elektrochemické techniky; Chemical modification of carbohydrates; kyselina N-acetylneuraminová; grafit; Glycoproteins